Consideraciones sobre la Guía Cubana de Hipertensión Arterial de 2017 - Ávila Cabreja, José A.; Fernández Massip, Haydée; Sosa González, Ismael; Fonseca Marrero, Carlos A. (CorSalud, 2018)
Consideraciones sobre la Guía Cubana de Hipertensión Arterial de 2017